PTH-019 The Effect Of Three Interventions On Colonoscopy Quality Outcomes - An Exemplar For Endoscopy Units. (9th June 2014) - Verma, AM; Dixon, A; Chilton, AP
Abstract : Introduction: Kettering General Hospital's endoscopy unit performs >1300 colonoscopies per annum (symptomatic, surveillance and bowel cancer screening). During 2012, three interventions took place in the unit. The vetting guidelines for requesting colonoscopy were updated to reflect BSG guidance for the management of iron deficiency anaemia and NICE guidelines for colorectal cancer. The aim was to reduce the number of inappropriate colonoscopies, especially in those patients not fit for colonoscopy. The information leaflets sent to patients pre-colonoscopy had a prompt added to urge patients to take the full dose of 4 sachets of Klean Prep (polyethylene glycol) to improve the diagnostic quality and exclusion value. Three colonoscopists who were not meeting key performance indicators stopped performing colonoscopy. This allowed the remaining operators to increase the number of colonoscopies they perform. We have audited the effects of these interventions individually and overall. Methods: We compared data from 2013 to 2011 to assess the impact of the intervention undertaken. To assess the impact of the change in vetting guidelines, we measured the number of patients with ASA grade 3 or 4 who underwent colonoscopy. To assess the impact of the change in patient information, we measured the number of sachets of Klean prep taken by patients and the assessment of the quality of bowel preparation. To assess the impact of certain operators stopping performing colonoscopy, we measured the number of operators (excluding trainees) who performed >100 colonoscopies per annum and those with caecal intubation rate (CIR) >90%. To measure the combined effect of the interventions, we looked at the combined CIR of all operators within the department. Results: Conclusion: All three interventions have caused improvements in measured outcomes. Fewer patients with significant co-morbidities are undergoing colonoscopy. The bowel preparation has improved and there is a statistically significant increase in the mean dose of Klean prep taken. The changes in the number of operators undertaking colonoscopy have allowed fewer operators to do more procedures. Intuitively, practice makes perfect and this along with the other interventions has significantly improved the combined CIR of all operators from 90.21 to 94.54% (p= <0.0001). The implementation of interventions outlined has been rewarding and is an exemplar to other endoscopy units on how to improve key quality outcomes of their colonoscopy practice. Disclosure of Interest: None Declared.